Takhrij Fikih dan Permasalahan Kontemporer - Meirison, Meirison; Saharuddin, Desmadi; Rosdialena, Rosdialena (AL-ISTINBATH : Jurnal Hukum Islam, 2020)
This paper aims to describe Takhrij as a medium for understanding the general rules established by imams that are built on the fiqh fiqh by induction and analyzing specific problems (furu 'fiqhiyah), this is what the takhrij ushul means for furu'.Takhrij also means to resolve differences furu 'fiqhiyah with the ushuliyah rules originating from the imams. It is expected to find a law that does not have the proposition shara 'by returning it to the rules and ushul. With a literature study and comparative approach to descriptive analysis, it is found that fiqh takhrij is also used to recognize the law that comes from a priest in a problem that has no text. Its can be made by comparing it with the same furu 'problem with the texts (qiyas), or comparing it with the understanding of Imam's texts or its generality. This is the furu takrij 'on furu'. Takhrij fiqh can be applied to contemporary problems such as loading and unloading insurance, inflation, copyright, furu 'and Syariah laws' in contemporary matters. The development of takhrij fiqh is dependent on the interaction of theory and practice in the existing field to produce solutions to contemporary problems.